Mengembangkan Sikap dan Praktik Belajar Mandiri: Alternatif Model Belajar-Mengajar Aktif dan Efektif - Mohammad Noor Syam (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
Independent learning is an alternative way in developing quality of human resources. It acknowledges children’s individual potentials and nature as human beings. Commonly implemented in laboratory schools, independent learning is developed on the basis of studies of educational theories and practices. It can be gradually and continously developed in elementary as well as secondary education. In short, such an alternative of learning types is worth considering in the pursuit of an active and effective teaching-learning process.